The bioactivity potential of Acmella paniculata plant extract in antioxidant activity by two different extraction methods / Rajina Shahmir Sivaraj ... [et al.] - Sivaraj, Rajina Shahmir; Mohamed Hanaphi, Roziana; Jafri, Nurul Afiqah; Mahadzir, Muhammad Naseem; Yusof, Rizana (Research Management Institute (RMI), 2023)
Widely used synthetic chemicals like heavy metals act as active compounds in personal care products such as shampoo, soap and cosmetics. These hazardous chemicals cause harmful threats to the environment and unintentionally lead to dangerous exposure towards human health. Thus, demands on natural organic compounds have increased nowadays. Bioactive compounds from plant extracts are well known to have intrinsic biological values that are relevant in promoting human health. There are numerous ways to extract these unique and important compounds involving techniques that are simple, environmentally friendly and efficient. The aim of this study is to highlight the biological potential of compounds from the local plant, Acmella paniculata in antioxidant activity. This small flowering shrub species is also known locally as Subang nenek. The first phase of this study involved the leaf extraction of A. paniculata performed by a common method known as Soxhlet extraction using methanol solvent and a simple centrifuged method using deep eutectic solvent (DES) which is a green solvent. Soxhlet method is a conventional procedure that takes longer time and involves specific equipments. However, this method has been used for many years as standard method due to its consistent results. Meanwhile, DES based centrifugation method is a new, innovative method for plant extraction with a fast procedure and minimal used of equipment. The second phase involved phytochemical screening and antioxidant activity testing. The phytochemical screening for A. paniculata leaf extract showed noticeable secondary metabolites such as alkaloids, tannins, terpenoids and steroids.